2018
DOI: 10.1017/rdc.2017.143
|View full text |Cite
|
Sign up to set email alerts
|

Large Variability of Dissolved Inorganic Radiocarbon in the Kuroshio Extension of the Northwest North Pacific

Abstract: Radiocarbon (14C) in dissolved inorganic carbon (DIC) was measured for water samples collected from six deep stations in the Kuroshio Extension (KE) region in the northwestern North Pacific in April–May 2015. Vertical profiles of Δ14C-DIC indicate that bomb-produced 14C was present from the surface to ~1500 m water depth. Large variations in Δ14C-DIC values (300‰) were observed at 500 m water depth among the stations and the differences were likely controlled by transport and mixing dynamics of different water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 44 publications
4
18
1
Order By: Relevance
“…The Keeling plot of DIC is linear and possessed a high coefficient with R 2 = 0.66 ( p < 0.001, n = 63), as determined by Model II regression (geometric mean regression) (Figure a), confirming that the main controls on the observed distributions of DIC and Δ 14 C‐DIC were hydrodynamic mixing processes within the SCS. The DIC Keeling plot in the SCS (slope = 3.5 × 10 6 ) is consistent with those obtained in the Kuroshio Extension region and the eastern NP (4 × 10 6 and 4.29 × 10 6 , respectively), confirming that DIC concentrations and Δ 14 C‐DIC can be used as conservative tracers of water mass movement and water parcel homogenization (Beaupré & Aluwihare, ; Ding et al, ), and thus the distribution of Δ 14 C‐DIC could be predicted by the solution mixing model in the SCS. If we use the average value of 49‰ for Δ 14 C‐DIC of the Kuroshio water mass in the upper 500 m depth (Stations C05 and C08) and −218‰ for Δ 14 C‐DIC of the NP deep water at depths deeper than 1,500 m (Figure a and Table S2), we calculated that 46–82% of the NP deep water could have been upwelled and mixed with Kuroshio water in the upper 250–700 m depth based on the mass balance, thus resulting in the observed Δ 14 C‐DIC profiles in the SCS, suggesting that water mixing in the upper 800 m depth in the basin of the SCS is quite dynamic and the ventilation by water exchange is more rapid in the upper 800 m depth than that in the deep basin water.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The Keeling plot of DIC is linear and possessed a high coefficient with R 2 = 0.66 ( p < 0.001, n = 63), as determined by Model II regression (geometric mean regression) (Figure a), confirming that the main controls on the observed distributions of DIC and Δ 14 C‐DIC were hydrodynamic mixing processes within the SCS. The DIC Keeling plot in the SCS (slope = 3.5 × 10 6 ) is consistent with those obtained in the Kuroshio Extension region and the eastern NP (4 × 10 6 and 4.29 × 10 6 , respectively), confirming that DIC concentrations and Δ 14 C‐DIC can be used as conservative tracers of water mass movement and water parcel homogenization (Beaupré & Aluwihare, ; Ding et al, ), and thus the distribution of Δ 14 C‐DIC could be predicted by the solution mixing model in the SCS. If we use the average value of 49‰ for Δ 14 C‐DIC of the Kuroshio water mass in the upper 500 m depth (Stations C05 and C08) and −218‰ for Δ 14 C‐DIC of the NP deep water at depths deeper than 1,500 m (Figure a and Table S2), we calculated that 46–82% of the NP deep water could have been upwelled and mixed with Kuroshio water in the upper 250–700 m depth based on the mass balance, thus resulting in the observed Δ 14 C‐DIC profiles in the SCS, suggesting that water mixing in the upper 800 m depth in the basin of the SCS is quite dynamic and the ventilation by water exchange is more rapid in the upper 800 m depth than that in the deep basin water.…”
Section: Discussionsupporting
confidence: 83%
“…The Δ 14 C‐DIC and DIC concentrations have been used as conservative tracers of water mass movement and water parcel homogenization in the ocean (Beaupré & Aluwihare, ; Ding et al, ; Key et al, ). The majority of DIC in the surface ocean (0–100 m) is from atmospheric CO 2 entering the ocean through air‐sea exchange and dissolved as carbonate species.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been obtained by previous studies focused on different regions in the ECS (Hung et al, 2003; and other marginal seas of the NP (Hung et al, 2007;Dai et al, 2009). In our recent study, we have reported that the depth concentrations of DIC and  14 C-DIC values in the ECS slope and the KE region showed conservative behavior and could be used as tracers of water mass movement and water parcel homogenization as predicted by the solution mixing model (Ge et al, 2016;Ding et al, 2018). In Fig.…”
Section: Process Controlling Doc Distribution In the Ecssupporting
confidence: 89%
“…The methods for DIC concentrations and  14 C-DIC measurements have been described in detail in separated papers for the samples collected during the same cruise (Ge et al, 2016;Ding et al, 2018). Briefly, DIC concentrations were measured using a Shimadzu TOC-L analyzer with the total IC mode.…”
Section: Chemical Analysismentioning
confidence: 99%
“…In this study, we use the radiocarbon content in dissolved inorganic carbon (DIC) to trace the movement of the Changjiang dilute water and the KBC subsurface water and their interactions off the Changjiang Estuary. Radiocarbon content in water DIC has been used to trace currents movement in the northwest Pacific (Ding et al, 2018;Ge et al, 2016;Tsuboi et al, 2011) and horizontal and vertical mixing processes in the South China Sea (Bolton et al, 2016;Ding et al, 2020;Gao et al, 2018). The vertical profiles of DIC Δ 14 C at the ECS continental slope have shown the upwelling of KC intermediate water onto the outer shelf (Ge et al, 2016).…”
mentioning
confidence: 99%